STEREOTYPICAL REPRESENTATION OF THE IMAGE OF A WOMAN IN PAREMIOLOGICAL UNITS (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
Stereotypes are formed in society and find expression in verbal form, i.e., in language. Language is not only a means of objectifying stereotypes, but also serves as a tool for reproducing them. Therefore, the study of linguistic units allows to examine stereotypes that are widespread in a society whose members use a given language